2004
DOI: 10.1021/ic049754v
|View full text |Cite
|
Sign up to set email alerts
|

Zn(II) Coordination to Polyamine Macrocycles Containing Dipyridine Units. New Insights into the Activity of Dinuclear Zn(II) Complexes in Phosphate Ester Hydrolysis

Abstract: Zn(II) binding by the dipyridine-containing macrocycles L1-L3 has been analyzed by means of potentiometric measurements in aqueous solutions. These ligands contain one (L1, L2) or two (L3) 2,2'-dipyridine units as an integral part of a polyamine macrocyclic framework having different dimensions and numbers of nitrogen donors. Depending on the number of donors, L1-L3 can form stable mono- and/or dinuclear Zn(II) complexes in a wide pH range. Facile deprotonation of Zn(II)-coordinated water molecules gives mono-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 72 publications
0
35
0
Order By: Relevance
“…31,90,112 Numerous research groups have reported Zn(II)Zn(II) hydrolase mimics. [14][15][16]18,20,22,90,92,101,[122][123][124][125][126][127] Bringing two Zn(II) ions in 132 The bidentate-bridging binding mode of the diphenyl phosphate was also proposed in solution using 31 P-NMR measurements because of the rather large shifts observed for the phosphate ester signal. 132 The separation of the two zinc centres in the biomimetics has been shown to be important.…”
Section: Dinuclear Zinc Hydrolase Mimicsmentioning
confidence: 99%
“…31,90,112 Numerous research groups have reported Zn(II)Zn(II) hydrolase mimics. [14][15][16]18,20,22,90,92,101,[122][123][124][125][126][127] Bringing two Zn(II) ions in 132 The bidentate-bridging binding mode of the diphenyl phosphate was also proposed in solution using 31 P-NMR measurements because of the rather large shifts observed for the phosphate ester signal. 132 The separation of the two zinc centres in the biomimetics has been shown to be important.…”
Section: Dinuclear Zinc Hydrolase Mimicsmentioning
confidence: 99%
“…Of note, the hydrolytic activity of the [Zn 2 L2(OH) 2 ] 2+ is only slightly lower than that reported for the dizinc complex with ligand 2 and among the highest observed with binuclear Zn(II) complexes [71]. For instance, the dizinc complexes with ligands not containing aromatic subunits, such as 3-5 in Scheme 1 [46][47][48], display a far lower ability in BNPP hydrolysis.…”
Section: Conversely the Monohydroxo Complex [Zn 2 L2(oh)]mentioning
confidence: 75%
“…BNPP hydrolysis promoted by mono-and dinuclear Zn(II) complexes is generally explained in terms of an "associative" mechanism [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50]71], in which the substrate approaches the Zn(II) complex and the oxygens of BNPP start associating with the electrophilic Zn(II) ion. A zincbound hydroxide operates a simultaneous nucleophilic attack to the phosphorus atom.…”
Section: Bis(p-nitrophenyl)phosphate Hydrolysismentioning
confidence: 99%
See 2 more Smart Citations